Tinjauan Penerapan Sanksi Kasapekang Di Desa Adat Dewasana Dalam Perspektif Hak Asasi Manusia (HAM) - Ida Bagus Gede Giri Putrayasa; Ni Nyoman Sukerti (International Forum of Researchers and Lecturers, 2023)
The purpose of writing this research is to find out the regulation of kasapekang sanctions and the implementation of kasepekang sanctions imposed on residents in Dewasana Traditional Village based on the perspective of Human Rights (HAM). The research that the researcher conducted was empirical research using a statutory approach, case approach, facts and comparisons. The results of the study show that the regulations that guarantee the existence of customary law communities are regulated according to Indonesian positive law in the 1945 Constitution article 18b paragraph 2 and also village awig-awig, especially the Dewasana Customary Village related to kasapekang sanctions are regulated in the village awig-awig in pawos 69. Kasepekang sanctions when viewed from a human rights perspective can lead to human rights violations because they are contrary to the formulations in the 1945 Constitution. For the implementation of kasepekang sanctions imposed on residents of Desa Adat Dewasana, it has been carried out in accordance with awig-awig pawos 69. In its implementation, the stage of imposing sanctions is considered quite mild, but it can also cause human rights violations.